2021
DOI: 10.31083/j.jin2002032
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in structural brain asymmetry of children with autism spectrum disorders

Abstract: specific diagnostic methods and treatments for males and females children with autism spectrum disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The reported multiregional asymmetry alterations are consistent with the notion that laterality is easily disrupted in patients with ASD (Maximo et al, 2014). In our study, the results showed that various GM asymmetry alterations were located in several clusters in the general ASD group, predominantly involving the temporal, frontal, and parahippocampal gyrus, which part overlapped with findings in previous studies, such as the parahippocampal gyrus having more leftward asymmetry (Li et al, 2021). However, in the postcentral gyrus, general ASD showed more rightward asymmetry; previous studies by Hau et al (2022) reported leftward asymmetry of the postcentral gyrus volume in ASD patients relative to the TD group.…”
Section: The Atypical Pattern Of Gm Asymmetry In the General Asd Groupsupporting
confidence: 91%
See 1 more Smart Citation
“…The reported multiregional asymmetry alterations are consistent with the notion that laterality is easily disrupted in patients with ASD (Maximo et al, 2014). In our study, the results showed that various GM asymmetry alterations were located in several clusters in the general ASD group, predominantly involving the temporal, frontal, and parahippocampal gyrus, which part overlapped with findings in previous studies, such as the parahippocampal gyrus having more leftward asymmetry (Li et al, 2021). However, in the postcentral gyrus, general ASD showed more rightward asymmetry; previous studies by Hau et al (2022) reported leftward asymmetry of the postcentral gyrus volume in ASD patients relative to the TD group.…”
Section: The Atypical Pattern Of Gm Asymmetry In the General Asd Groupsupporting
confidence: 91%
“…Abnormal structural asymmetries in patients with ASD have been reported to be widely distributed across various brain regions ( Maximo et al, 2014 ). Examples include significantly increased rightward asymmetry in the inferior parietal lobule, auditory cortex ( Floris et al, 2016 ), posterior superior temporal gyrus ( Gage et al, 2009 ), and lateral orbitofrontal surface area ( Postema et al, 2019 ) and reduced rightward asymmetry in the medial orbitofrontal surface area, putamen volume, and the parahippocampal gyrus ( Postema et al, 2019 ; Li et al, 2021 ). The reported multiregional asymmetry alterations are consistent with the notion that laterality is easily disrupted in patients with ASD ( Maximo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…While environmental factors like family environment or intense training (e.g., music practice [ 55 ]) are known to modulate brain anatomy [ 56 ], little is known about schooling experience. More specifically, recent work has shown that while the cortical thickness (CTh) of the left and right hemispheres is globally similar (i.e., symmetric), between-hemisphere variations (i.e., asymmetry index) can be observed, and they provide insights about typical or atypical neurodevelopment [ 17 , 19 , 57 , 58 ]. The current study specifically contrasted CTh asymmetries in 4–18 y.o.…”
Section: Discussionmentioning
confidence: 99%
“…Past work on brain asymmetry was mostly performed using adult participants’ data, reporting rather symmetric hemispheres [ 16 , 17 ]. While other studies have investigated asymmetry in atypical children [ 19 , 57 , 58 ], few report developmental data on CTh asymmetry metrics. Hill et al (2010) compared healthy babies with healthy adults and found no difference in terms of cortical folding patterns and hemispherical depth asymmetries.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature [14] multi-site data with 900 subjects was used, and about 200 subjects from 2 sites were included in the paper [15]. Papers [16,17] show that, compared with a small number of samples in a single area, MRI data of the same kind of brain diseases in multiple sites can provide more sufficient statistical information, so as to better explore the functional mode of the brain structure of a patient. By studying the papers [18][19][20], it can be found that compared with the patients in a single area, the population distribution of the same disease in different regions is diverse.…”
Section: Introductionmentioning
confidence: 99%